At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
g(x) = -3x + 4
g(-2) = -3 x (-2) + 4 = 6 + 4 = 10
g(4) = -3 x 4 + 4 = -12 + 4 = -8
Therefore, D is the correct answer.
g(-2) = -3 x (-2) + 4 = 6 + 4 = 10
g(4) = -3 x 4 + 4 = -12 + 4 = -8
Therefore, D is the correct answer.
Answer:
D. The value of g(-2) is larger than the value of g(4).
Step-by-step explanation:
Given : Given the function g(x) = -3x + 4, compare and contrast g(-2) and g(4).
To find : Choose the statement that is true concerning these two values.
Solution : We have given that
g(x) = -3x + 4
g (-2) = -3 ( -2) + 4.
g (-2) = 6 + 4
g (-2) = 10 .
Now,
g (4) = -3 ( 4) + 4.
g (4) = -12 +4 .
g (4) = -8.
g (-2) > g (4)
10 > -8 .
Therefore, D. The value of g(-2) is larger than the value of g(4).
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.